Comparative Effects of Elettaria cardamomum Essential Oil and Its Nanoliposomal State on Mortality of Anopheles stephensi Larvae - Mohammad Djaefar Moemenbellah-Fard; Zahra-Sadat Hosseinizadeh; Hamzeh Alipour; Roghayeh Heiran; Marzieh Shahriari-Namadi; Abdolmajid Ghasemian; Mahmood Osanloo (Tehran University of Medical Sciences, 2024)
Background: Malaria has remained the most dreadful vector-borne disease; hence, vector control is the most affordable and achievable approach to mitigate the disease burden. Due to the emergence of resistance and environmental pollution, herbal larvicides are considered an alternative to chemical types. Also, nanotechnology has been proposed as a promising solution to improve the efficiency of plant larvicides. This study aimed to develop an effective herbal larvicide.   Methods: The chemical composition of Elettaria cardamomum essential oil (EO) was first investigated. Nanoliposomes containing the EO were then prepared using the ethanol injection method. After that, the larvicidal efficacy of the EO and its liposomal state were compared against Anopheles stephensi in laboratory conditions. Results: Alpha-terpinyl acetate (77.59%), eucalyptol (4.38%), nerolidol (2.96%), linalool (1.77%), and limonene (1.69%) were the five major compounds of the EO. Nanoliposomes containing the EO with a particle size of 73±5 nm and a zeta potential of -16.3±0.8 mV were prepared. Additionally, the ATR-FTIR analysis verified the successful loading of the EO into nanoliposomes. The larvicidal activity of nanoliposomes exhibited remarkable potency, with an LC50 value of 14.35 (10-18) µg/mL, significantly more potent than the non-formulated EO, which had an LC50 value of 33.47 (28-39) µg/mL against Anopheles stephensi larvae. Conclusion: The nanoliposomes containing E. cardamomum EO showed promising efficacy against An. stephensi larvae. It could thus be considered for further application against other species of mosquitoes.